B lymphocytes can be activated to act as antigen presenting cells to promote anti-tumor responses - Rossetti, Renata Ariza Marques; Lorenzi, Noely Paula Cristina; Yokochi, Kaori; Rosa, Maria Beatriz Sartor de Faria; Benevides, Luciana; Margarido, Paulo Francisco Ramos; Baracat, Edmund Chada; Carvalho, Jesus Paula; Villa, Luisa Lina; Lepique, Ana Paula (PLOS ONE, 2018)
Immune evasion by tumors includes several different mechanisms, including the inefficiency of antigen presenting cells (APCs) to trigger anti-tumor T cell responses. B lymphocytes may display a pro-tumoral role but can also be modulated to function as antigen presenting cells to T lymphocytes, capable of triggering anti-cancer immune responses. While dendritic cells, DCs, are the best APC population to activate naive T cells, DCs or their precursors, monocytes, are frequently modulated by tumors, displaying a tolerogenic phenotype in cancer patients. In patients with cervical cancer, we observed that monocyte derived DCs are tolerogenic, inhibiting allogeneic T cell activation compared to the same population obtained from patients with precursor lesions or cervicitis. In this work, we show that B lymphocytes from cervical cancer patients respond to treatment with sCD40L and IL-4 by increasing the CD80+CD86+ population, therefore potentially increasing their ability to activate T cells. To test if B lymphocytes could actually trigger anti-tumor T cell responses, we designed an experimental model where we harvested T and B lymphocytes, or dendritic cells, from tumor bearing donors, and after APC stimulation, transplanted them, together with T cells into RAG1-/- recipients, previously injected with tumor cells. We were able to show that anti-CD40 activated B lymphocytes could trigger secondary T cell responses, dependent on MHC-II expression. Moreover, we showed that dendritic cells were resistant to the anti-CD40 treatment and unable to stimulate anti-tumor responses. In summary, our results suggest that B lymphocytes may be used as a tool for immunotherapy against cancer.